Bioactive content of six passion fruit genotypes cultivated in southern Brazil - Diego Weber; Jessica Fernanda Hoffmann; Caroline Farias Barreto; Giovana Paula Zandoná; Jair Costa Nachtigal; Fabio Clasen Chaves; Marcelo Barbosa Malgarim (Bioscience Journal, 2021)
Passion fruit production in Brazil is concentrated in tropical regions, however, recently production has expanded to regions with temperate climate. Cultivar performance in different climate and soil can lead to variation in the contents of bioactive compounds in the juice and rind of the fruit. This study characterized the bioactive content of passion fruit rind and juice of six passion fruit genotypes (‘Catarina Roxo’, ‘Catarina’, ‘Urussanga’, ‘BRS Gigante Amarelo’, ‘BRS Rubi do Cerrado’, and ‘BRS Sol do Cerrado’) cultivated in southern Brazil. Phenolic, flavonoid, anthocyanin, carotenoid, and ascorbic acid contents and the antioxidant potential of each fruit portion from each genotype were evaluated. Fruit composition varied with genotype and evaluated tissue. Bioactive compound contents were greatest in the rind of ‘Urussanga’ and ‘Catarina’, whereas the juice of ‘BRS Sol do Cerrado’ and ‘Catarina Roxo’ had the greatest bioactive content. Given cultivar and tissue variability for bioactive content, postharvest use of passion fruit will determine the choice of cultivar to obtain a product with maximum bioactive compounds. Passion fruit genotypes evaluated in this study have shown to be potential sources of bioactive compounds. Fruit rind has the potential to be explored in the scientific and technological scope, due to its high amounts of phenolic compounds and antioxidant activity.